Gaya Bahasa Enkyokuhou dalam Novel Nihon Kogyou Ginkou Karya Ryo Takasugi - Rudi Hartono Manurung (Lingua Cultura, 2015)
Research aimed to present conversations that were used mostly by subordinates (buka) to their superiors (joshi). The research applied qualitative method with interview and novel Nihon Kogyou Ginkou by Ryo Takasugi to understand the jougekankei concept in enkyokuhou figure of speech. Analysis used interpretative and descriptive method. It can be concluded that enkyokuhou has five functions. They are to emphasize claims, emphasize on demands, state indirect thought or passive request, state satire, and replace words or objects or events with another words.